2021
DOI: 10.1186/s13045-021-01070-w
|View full text |Cite
|
Sign up to set email alerts
|

Targeting neddylation E2s: a novel therapeutic strategy in cancer

Abstract: Ubiquitin-conjugating enzyme E2 M (UBE2M) and ubiquitin-conjugating enzyme E2 F (UBE2F) are the two NEDD8-conjugating enzymes of the neddylation pathway that take part in posttranslational modification and change the activity of target proteins. The activity of E2 enzymes requires both a 26-residue N-terminal docking peptide and a conserved E2 catalytic core domain, which is the basis for the transfer of neural precursor cell-expressed developmentally downregulated 8 (NEDD8). By recruiting E3 ligases and targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 133 publications
0
21
0
Order By: Relevance
“…Surprisingly, cofilin (K112R) and wild type (WT) cofilin in the presence of MLN4924 maintained their interactions with SSH1L, LIMK1, and CIN, as measured by co-precipitation with biotin-tagged cofilins. As mentioned previously, cofilin binds cooperatively to F-actin with severing occurring at the junctions between cofilin saturated and unbound regions [12,110]. In the presence of the neddylation inhibitor, F-actin binding of both cofilin (K112R) and WT cofilin increased.…”
Section: Ubiquitinylation and Neddylationmentioning
confidence: 54%
“…Surprisingly, cofilin (K112R) and wild type (WT) cofilin in the presence of MLN4924 maintained their interactions with SSH1L, LIMK1, and CIN, as measured by co-precipitation with biotin-tagged cofilins. As mentioned previously, cofilin binds cooperatively to F-actin with severing occurring at the junctions between cofilin saturated and unbound regions [12,110]. In the presence of the neddylation inhibitor, F-actin binding of both cofilin (K112R) and WT cofilin increased.…”
Section: Ubiquitinylation and Neddylationmentioning
confidence: 54%
“…Expanding the analysis to additional MPM cells, including at least two MPM for each histotype, one BAP1 + and one BAP1 - MPM, we found that MLN4924 decreased activity of UBE2M (Fig. 3 B), a component of the enzymatic system required for cullin 1 neddylation [ 22 ]. While MLN4924 impaired the neddylation/UBE2M system, it only slightly increased proteasome activity (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Increasing evidence suggests that neddylation is aberrantly activated in a wide range of tumor types, consequently affecting tumor progression and altering the TME ( Xie et al, 2021 ; Zhou et al, 2021 ). Further research on neddylation-related genes is warranted to provide new treatment strategies for cancer treatment ( Zheng et al, 2021 ). Lung cancer is one of the leading causes of human death worldwide and has a high incidence and mortality rate.…”
Section: Discussionmentioning
confidence: 99%